2015
DOI: 10.1177/1533317515603818
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives About Health Care Provision in Dementia Care in Spain

Abstract: The family is a key element in successful care coordination during dementia care provision. New effective strategies including self-management and emergent roles, such as case managers, could bring great benefits to people with dementia, caregivers, and health care providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(44 citation statements)
references
References 34 publications
2
42
0
Order By: Relevance
“…We all seem to do a little bit of dementia each, but we don't have perfectly dedicated people and if we do they're very secondary care positioned. -GP (Newton et al, 2016) But while having multiple professionals involved could complicate expectations and responsibilities of the professionals (Gilmour et al, 2003;Risco et al, 2015), one study observed that:…”
Section: Expectations Of Care and Of The Role In The Triadmentioning
confidence: 99%
See 1 more Smart Citation
“…We all seem to do a little bit of dementia each, but we don't have perfectly dedicated people and if we do they're very secondary care positioned. -GP (Newton et al, 2016) But while having multiple professionals involved could complicate expectations and responsibilities of the professionals (Gilmour et al, 2003;Risco et al, 2015), one study observed that:…”
Section: Expectations Of Care and Of The Role In The Triadmentioning
confidence: 99%
“…Carers and people living with dementia reported that if there were too many professionals offering advice and getting involved it could lead to confusion over tasks and professional involvement (Gilmour et al, 2003;Risco et al, 2015). Continuity was reduced when there was a lack of services, which resulted in increased risk of harm, and carers finding themselves stretched in order to provide more care (Stephan et al, 2018;Toot et al, 2013).…”
Section: Continuity Of Carementioning
confidence: 99%
“…The articles comprised three reviews of dementia care and four primary studies. Two of the primary studies explored views of people living with dementia and health and social care staff in the UK (Dening, Greenish, Jones, Mandal, & Sampson, 2012) and in Spain (Risco et al, 2016). Melin Emilsson (2009) employed a comparative approach to investigating views of health and social care staff in long-term care facilities in France, Portugal, and Sweden, while Gotts et al (2016) conducted a survey of commissioners of end-of-life care in the UK.…”
Section: Characteristics Of Items Selected For Synthesismentioning
confidence: 99%
“…The findings highlight that most healthcare systems in Europe are designed to tackle distinct illnesses without much scope for interaction between different parts of systems. Delayed diagnoses, care in inappropriate and distressing settings, and unnecessary early transfers to long-term care facilities embody dementia care provided within disjointed care systems (Houghton et al, 2016;Risco et al, 2016;Turner et al, 2017). Fragmentation is apparent not only in the system-based approaches to providing care but also in the hegemony of biomedical diagnoses, which focus on the condition and its management with little or no concern for social health of the person with dementia (de Vugt & Dr€ oes, 2017).…”
Section: Implications For Policy Research and Practicementioning
confidence: 99%
“…Mediterranean cultures tend to place similar emphasis on the importance of the family and older people are still helped and cared for by the youngest offspring at home. Consequently, admission of a family member to a long-term care institution can even cause feelings of failure and disappointment within the family (Risco et al 2015). Many international studies have been conducted on the risk factors associated with admission to a long-term care institution (Rongve et al 2014; Tam-Tham et al 2013).…”
Section: Introductionmentioning
confidence: 99%